KEGAGALAN PENGENDALIAN DIABETES MELLITUS TIPE II DITINJAU DARI FAKTOR PREDISPOSISI - Khusnul Diana; Amalia Purnamasari Zainal; Setaiawati Fadhilah Zainal; Muhammad Rinaldhi Tandah; Dhea Puspita; Nurul Ambianti (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Failure to control type II diabetes mellitus (DM) has a serious impact on the quality of life and health of DM patients. One of the factors that can influence the failure to control DM is predisposing factors. This study aims to determine predisposing factors including gender, education level, age, smoking, occupation, sports activities, long-suffering, knowledge, and behavior that influence failure to control type II DM. The research method used was descriptive analysis with cross-sectional data collection. This research used a purposive sampling technique and the patients used were 179 respondents. Data was collected using the Diabetes Knowledge Questionnaire (DKQ-24) questionnaire and the Self-Management Diabetes Mellitus (SMDM) questionnaire instrument. The data analysis used is bivariate and multivariate. The results of the bivariate analysis show that the variables that influence the failure to control Type II DM are the length of suffering (p = 0.000), behavior (p = 0.004), sports activities (p = 0.029), and work (p = 0.020). The results of the multivariate analysis of the dominant factors influencing failure to control type II DM are long-suffering with a value of OR = 6.956, behavior with a value of OR = 4.156, knowledge with a value of OR = 2.947, sports activities with a value of OR = 0.690, so it can be concluded that the variable long-suffering is The main factor in the failure to control type II DM because it can increase the risk of complications such as pancreatic cell damage and insulin resistance.